Group Intelligence: A Distributed Cognition Perspective - Mansour, O. (2009 International Conference on Intelligent Networking and Collaborative Systems, 2009)
The question of whether intelligence can be attributed to groups or not has been raised in many scientific disciplines. In the field of computer-supported collaborative learning, this question has been examined to understand how computer-mediated environments can augment human cognition and learning on a group level. The era of social computing which represents the emergence of Web 2.0 collaborative technologies and social media has stimulated a wide discussion about collective intelligence and the global brain. This paper reviews the theory of distributed cognition in the light of these concepts in an attempt to analyze and understand the emergence process of intelligence that takes place in the context of computer-mediated collaborative and social media environments. It concludes by showing that the cognitive organization, which occurs within social interactions serves as a catalyst for intelligence to emerge on a group level. Also a process model has been developed to show the process of collaborative knowledge construction in Wikipedia that characterizes such cognitive organization.